Astrocytic Ephrin-B1 Controls Synapse Formation in the Hippocampus During Learning and Memory - Nguyen, Amanda Q.; Koeppen, Jordan; Woodruff, Simone; Mina, Karen; Figueroa, Zoe; Ethell, Iryna M. (Frontiers in Synaptic Neuroscience, 2020)
Astrocytes play a fundamental role in synapse formation, pruning and plasticity, which are associated with learning and memory. However, the role of astrocytes in learning and memory is still largely unknown. Our previous study showed that astrocyte-specific ephrin-B1 knock-out (KO) enhanced but ephrin-B1 overexpression (OE) in hippocampal astrocytes impaired contextual memory recall following fear conditioning. The goal of this study was to understand the mechanism by which astrocytic ephrin-B1 influences learning; specifically, learning-induced remodeling of synapses and dendritic spines in the CA1 hippocampus using fear-conditioning paradigm. While we found a higher dendritic spine density and clustering on c-Fos-positive (+) neurons activated during contextual memory recall in both wild-type (WT) and KO mice, overall spine density and mEPSC amplitude were increased in CA1 neurons of KO compared to WT. In contrast, ephrin-B1 overexpression in hippocampal astrocytes impaired dendritic spine formation and clustering, specifically on c-Fos(+) neurons, coinciding with an overall decrease in vGlut1/PSD95 co-localization. Although astrocytic ephrin-B1 influenced learning-induced spine formation, the changes in astrocytic ephrin-B1 levels did not affect spine enlargement as no genotype differences in spine volume were observed between trained WT, KO and OE groups. Our results suggest that a reduced formation of new spines rather than spine maturation in activated CA1 hippocampal neurons is most likely responsible for impaired contextual learning in OE mice due to abundantly high ephrin-B1 levels in astrocytes. The ability of astrocytic ephrin-B1 negatively influence new spine formation during learning can potentially regulate new synapse formation at specific dendritic domains and underlie memory encoding.